Effects of tri-frequency ultrasonic vacuum-assisted ethanol pretreatment on infrared drying efficiency, qualities and microbial safety of scallion stalk slices. Issue 12 (1st September 2022) - Zhou, Cunshan; Cai, Zhe; Wang, Xule; Feng, Yabin; Xu, Xin; Yagoub, Abu ElGasim A.; Wahia, Hafida; Ma, Haile; Sun, Yanhui
Abstract: This paper aims to evaluate the impact of simultaneous tri-frequency ultrasound (20 + 40 + 60 kHz) combined vacuum (0.6 bar) assisted ethanol (75%) pretreatment on the infrared drying process, qualities (rehydration, flavor, surface color), and microbial safety of scallion stalk slices. The slices were pretreated with different methods, using ethanol, vacuum (Water + VC), vacuum-assisted ethanol (Ethanol + VC), ultrasound (Water + US), ultrasound-assisted ethanol (Ethanol + US), ultrasonic vacuum (Water + USVC), and ultrasonic vacuum-assisted ethanol (Ethanol + USVC). It was found that Ethanol + USVC pretreatment significantly reduced the drying time and showed better flavor retention and antibacterial effect, and the slices produced showed moderate rehydration ratio (7.83) and surface color change (8.94).